The Saraswati flows on the continuity of Indian culture - Lal, B.B. (New Delhi Aryan Books International, 2002)
The book deals with two major controversies relating to India's past. The author shows that there are compelling geographical data in the Rigveda itself which unambiguously show that the Rigvedic Sarasvati is none other than the present-day Sarasvati-Ghaggar combine which flows through Haryana and Punjab.;Second, it has vociferously been orchestrated that the Aryans invaded India, as a result of which the Harappan Civilization became extinct. The author shows that there is no evidence whatsoever to suggest any invasion, much less by the Aryans.
Keywords: Indus civilization